Nanomedicine for the reduction of the thrombogenicity of stent coatings - Varvara C Karagkiozaki; Stergios D Logothetidis; Spyridon N Kassavetis; et al (International Journal of Nanomedicine, 2010)
Varvara C Karagkiozaki1,2, Stergios D Logothetidis2, Spyridon N Kassavetis2, George D Giannoglou11Aristotle University of Thessaloniki, Medical School, AHE PA University General Hospital, 1st Cardiology Department, Cardiovascular Engineering and Atherosclerosis Laboratory, Greece; 2Aristotle University of Thessaloniki, Physics Department, Laboratory for Thin Films – Nanosystems and Nanometrology (LTFN), GreeceAbstract: The treatment of patients with drug-eluting stents (DES) continues to evolve with the current emergence of DES technology that offers a combination of pharmacological and mechanical approaches to prevent arterial restenosis. However, despite the promising short-term and mid-term outcomes of DES, there are valid concerns about adverse clinical effects of late stent thrombosis. In this study, we present an example of how nanomedicine can offer solutions for improving stent coating manufacturing, by producing nanomaterials with tailored and controllable properties. The study is based on the exploitation of human platelets response towards carbon-based nanocoatings via atomic force microscope (AFM). AFM can facilitate the comprehensive analysis of platelets behavior onto stent nanocoatings and enable the study of thrombogenicity. Platelet-rich plasma from healthy donors was used for the real-time study of biointerfacial interactions. The carbon nanomaterials were developed by rf magnetron sputtering technique under controllable deposition conditions to provide favorable surface nanotopography. It was shown that by altering the surface topography of nanocoatings, the activation of platelets can be affected, while the carbon nanocoatings having higher surface roughness were found to be less thrombogenic in terms of platelets adhesion. This is an actual solution for improving the stent coating fabrication.Keywords: stents nanomedicine, carbon coating, atomic force microscopy platelets nanotechnology